An investigation of the coupling coordination of a regional agricultural economics-ecology-society composite based on a data-driven approach. (October 2022) - Liu, Fan; Wang, Cui; Luo, Muchen; Zhou, Shuling; Liu, Conghu
Highlights: Presents a data-driven measurement, evaluation, and identification method. Uses a coupling coordination degree model for three regional agriculture subsystems. Suggests ways to reduce costs, increase social support, and enhance competitiveness. Abstract: This study aims to evaluate the relationship between the agriculture economy environment, and society from the perspective of system theory and then put forward targeted suggestions for sustainable development of Anhui's agriculture in China. Based on the collection of relevant data and the objective weighting of indicators, the entropy weight method is used to measure the comprehensive development level of regional agriculture. The coupling coordination degree model is employed to evaluate the coupling coordination level among the three subsystems of regional agriculture. The obstacle degree model is used to identify the key obstacle factors. The case study results show that the main obstacles of the coordination system are the use of pesticides, the number of agricultural scientific and technological achievements, the application of agricultural plastic film, the number of farmers' technical training schools, and the proportion of animal husbandry. Accordingly, the paper posits suggestions, such as reducing the input of pesticides and agricultural plastic films in agricultural production, improving the social support level of agricultural science, technology, and education, and enhancing the competitiveness of animal husbandry in the Anhui Province. This study provides theoretical and methodological support for the coupled and coordinated development of regional agricultural economy, ecology and society(EES).